Analysis of patents in the teaching of natural science disciplines - Shishonok, Margarita V. (University Pedagogical Journal, 2023)
The author’s experience of creating and implementing analytical reviews of modern patents into the educational process is presented. The actuality and effectiveness of including reviews in educational books, lectures, and creative assignments within the framework of controlled independent work of students are substantiated. It is proposed to create an educational product in the form of a knowledge base.